Determination of Natural Ventilation Pressure and Shaft Resistance by the Motive Column Method - C. J. Hall (Canadian Institute of Mining, Metallurgy and Petroleum, 1968)
This paper presents a basic motive column analysis of natural ventilation and shaft resistance, using the density depth diagram. The method makes use of tables showing the state of the air as determined by thermodynamic analysis. Several theoretical examples are given.